Indeks Kepuasan Masyarakat (IKM) terhadap Kualitas Pelayanan Publik di Puskesmas Oepoi Kota Kupang - Vivi Nesimnasi; Petrus Romeo; Enjelita M. Ndoen (Universitas Nusa Cendana, 2019)
The Public Satisfaction Index (IKM) is one of the methods used to determine the quality of public services through public perception. Public services provided by the Kupang City Oepoi Community Health Center (Puskesmas Oepoi) have not met yet community expectations. The preliminary observations found several problems regarding health services rendered by Puskesmas Oepoi, such as inadequate facilities and infrastructure, limited service time, insufficient human resources, and unsatisfying handling complaints and suggestions. These, consequently, could reduce public satisfaction, which will ultimately lead to a decline in the quality of Puskesmas Oepoi public services. This study aimed to determine the IKM toward the quality of public services in Puskesmas Oepoi Kupang City. The study used a quantitative descriptive survey approach. The number of samples was 96 respondents obtained by accidental sampling technique. The data analysis technique used the guidelines of Community Satisfaction Survey consisting of nine IKM indicators. The results showed that the satisfaction level and quality of services provided by Puskesmas Oepoi Kupang City in 2019 were at the